1993
DOI: 10.2307/3345405
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Textural and Timbral Factors on the Ability of Music Majors to Detect Performance Errors

Abstract: The purpose of this study was to investigate the effect of textural and timbral factors on graduate and undergraduate music majors' ability to detect performance errors. Specifically, subjects' discrimination of pitch and rhythm errors in music excerpts that were counterbalanced for error type, textural placement of errors (soprano, alto, tenor, and bass voices), and timbre (single and multiple) was examined. In the development of a stimulus audiotape for error detection, the Yamaha SY77 digital synthesizer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 8 publications
3
46
1
Order By: Relevance
“…Further study using a larger participant pool and greater control for preparation method seems warranted. Authors of previous research have suggested that rhythm errors were identified correctly more often than pitch errors and that participants' abilities to detect errors were greater when textures were simpler, as opposed to more complex (Byo, 1993(Byo, , 1997Crowe, 1996;Mount, 1982;Sheldon, 1998). The results of the current research indicated that there was a significant interaction between error types (rhythm/pitch) and ensemble textures (full ensemble/single section).…”
Section: Discussionsupporting
confidence: 46%
“…Further study using a larger participant pool and greater control for preparation method seems warranted. Authors of previous research have suggested that rhythm errors were identified correctly more often than pitch errors and that participants' abilities to detect errors were greater when textures were simpler, as opposed to more complex (Byo, 1993(Byo, , 1997Crowe, 1996;Mount, 1982;Sheldon, 1998). The results of the current research indicated that there was a significant interaction between error types (rhythm/pitch) and ensemble textures (full ensemble/single section).…”
Section: Discussionsupporting
confidence: 46%
“…That error detection may not be a skill into which other peripheral competencies (such as ear training) may be easily transferred or synthesized (Brand & Bursed, 1981;Byo, 1993Byo, , 1997DeCarbo, 1982;Doane, 1989;Forsythe & Woods, 1983;Gonzo, 1971;Larson, 1977;Ramsey, 1979) suggests that when such instruction is given outside the context of conducting and error detection, its usefulness in these activities is not immediately apparent to the learner. These results might imply that a "peripheral activity" such as aural skills development or ear training, when addressed within instructional time allotted for conducting training using materials that are context-specific, might be more readily viewed as something that enhances accuracy in error detection.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that although it uses certain abilities that may have been cultivated through discrete and tangential activities (e.g., ear training, music theory, private instrumental instruction, ensemble participation), error detection may be a skill into which other peripheral competencies may not be easily transferred or synthesized (Brand & Bursed, 1981;Byo, 1993Byo, , 1997DeCarbo, 1982;Doane, 1989;Forsythe & Woods, 1983;Gonzo, 1971;Larson, 1977;Ramsey, 1979). Brand and Bursed (1981) argue that error-detection abilities must be addressed separately from ear training and theory venues and treated as a unique skill that should be taught with the specific goal of discriminate hearing.…”
mentioning
confidence: 99%
“…Regression procedures were then performed for the significant variables. Four groups of predictor variables were identified, as related to the subjects' discrimination skills: The purpose of a study by Byo (1993) Correct four-line scores for each of the two excerpts were prepared. All subjects listened to the error detection audiotape while indicating on score copies the errors they perceived to have occurred.…”
mentioning
confidence: 99%